Moral and Social Education of the Messenger of Allah (SAW): A Study of the Book of Ar-Rahiq Al-Makhtum - Arsyad, Junaidi; Hanum OK, Azizah; Muharrir , Muharrir (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2025)
This research looks for and analyzes the moral and social educational values of the Prophet Muhammad SAW as referred to Sheikh Shafiyyurrahman Al-Mubarakfuri in Ar-Rahiq Al-Makhtum. Using a qualitative methodology, this study adopts historical and biographical approaches to reconstruct the educational practices of Prophet Muhammad to identify their relevance to contemporary educational needs. Primary data are extracted from Ar-Rahiq Al-Makhtum, augmented with secondary data comprising academic publications and books selected based on their veracity and pertinence to the last decade. Data were analyzed thematically to determine core values distilled into categories of moral education (e.g., piety, honesty, patience) and social education (e.g., tolerance, responsibility, compassion). There are eight ethical values derived from the findings: piety, respect for parents, honesty, trustworthiness, intelligence, effective communication, justice, patience as well as social values including socialization, common communication, tolerance, mutual assistance, leadership, loyalty, and accountability. Values embodied by Prophet Muhammad that are equipped to help build character in contemporary situations. These values can be adapted to other fields, including education, leadership, and community relations, according to the study. This study contributes to the broader discourse on Islamic education that links the historical significance of Prophet Muhammad's teachings with contemporary character education theories. It emphasizes the need to incorporate spiritual, intellectual and social aspects into contemporary educational systems. Interestingly, this model is based on Ar-Rahiq Al-Makhtum, from which these values can be drawn, and can even be applied to a practical scale.